Misja wojsk ISAF w Afganistanie - zagrożenia typu „Green on Blue” - Machniak, Arkadiusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The terrorist attacks in New York on 11th September 2001 resulted in a new method of armed conflict which was asymmetric in character, on this occasion in Afghanistan. The ISAF faced the Taliban – a rival who had an advantage because of local knowledge and help from some of the neighbouring countries, such as Pakistan, and international terrorist organizations such as Al-Qaeda. The Taliban maintained surveillance on the ANSF which supported ISAF. As a result, attacks described as green on blue happened which were caused also by a conflict of a cultural and religious basis between Afghan soldiers and ISAF soldiers. Due to its unpredictability and the impossibility of stating its area and time, they became one of the biggest dangers for ISAF soldiers during that difficult mission.
THE ISAF MISSION IN AFGHANISTAN – THE DANGER OF ‘GREEN ON BLUE’ ATTACKS
Keywords: green on blue attacks; Taliban; ISAF; coalitions; Afghanistan